MIDWIFERY CARE FOR MRS. R WITH IUFD AT KLINIK PRATAMA SAM - waruwu, Apriyanis; Nur Azizah; Waruwu , Niska Wati; Gultom , Yenny; Ginting , Saminah (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Maternal and fetal health is an important aspect of reproductive health services. Pregnancy complications may lead to adverse outcomes, including intrauterine fetal death (IUFD), which has significant physical and psychological effects on the mother. Therefore, comprehensive midwifery care is required to ensure proper management and emotional support. Objectives: This study aimed to provide midwifery care for Mrs. R with Intrauterine Fetal Death (IUFD) at Klinik Pratama Sam in 2026 using the seven-step Varney midwifery management approach and SOAP documentation. Methods: The research method used was a descriptive study with a case study approach. Data were collected through interviews, observations, physical examinations, obstetric examinations, and medical record review. Results: Mrs. R was a 38-year-old woman with obstetric status G2P1A0 at 23 weeks and 3 days of gestation. She was diagnosed with IUFD based on the absence of fetal movement, fundal height not matching gestational age, and no fetal heart sounds. The midwifery interventions included maternal monitoring, intravenous Ringer Lactate administration, preparation for delivery management, and psychological support. The patient’s condition remained stable and she showed acceptance of her condition with strong family support. Conclusions: the implementation of comprehensive midwifery care using Varney’s seven-step approach is effective in managing IUFD cases and providing both physical and psychological support to the mother.